Antisepsis and Asepsis and how They Shaped Modern Surgery. Issue 6 (June 2018) - Nakayama, Don K.
Surgical antisepsis and asepsis established the standard of using scientific evidence to determine surgical practice. The microbiological discoveries of Louis Pasteur (1822–1895) were the inspiration for Joseph Lister's (1827–1912) use of carbolic acid as an antiseptic on surgical wounds. German and Swiss surgeons invented aseptic surgical practice based on the studies of Robert Koch (1843–1910), a life-saving revolution in medicine as profound as anesthesia. Together they changed human history, sparing millions the horrors of hospital gangrene and making the entire body accessible to surgical intervention. In the United States, surgeons followed the lead of their brethren across the Atlantic. Americans, characteristically pragmatic, naturally resisted what they saw as unnecessary complexity in Listerism. Once they accepted germ theory, the undeniable scientific evidence led to the rapid acceptance of asepsis. Among the wide-ranging effects of this transition in practice were the creation of the current model of the academic department of surgery and the modern concept of surgical professionalism.